Contemporary radio art and spatial politics: the critical radio utopias of Anna Friz - Ouzounian, G (Intellect, 2008)
The article explores the work of the Canadian sound artist Anna Friz over the last decade. Her work deals explicitly with issues of technology and the relative absence of women's voices on radio. Exploring her work as a composer, installation artist, instrumentalist, performance artist and storyteller, and contextualising these practices within feminist critiques and radio conventions, the article explores Friz's self-reflexive radio. Ideas of supermodernity, displacement and critical utopia are deployed to discuss specific pieces of Friz's work in relation to identity and space. The article argues that Friz reconfigures the radio as a site of resistance to dominant constructions of contemporary globalised space and cultures, the politics of informational capitalism and the uneven flows that these cultures and politics engender.